2016
DOI: 10.15252/embr.201642738
|View full text |Cite
|
Sign up to set email alerts
|

Bin1 and CD 2 AP polarise the endocytic generation of beta‐amyloid

Abstract: The mechanisms driving pathological beta-amyloid (Ab) generation in late-onset Alzheimer's disease (AD) are unclear. Two late-onset AD risk factors, Bin1 and CD2AP, are regulators of endocytic trafficking, but it is unclear how their endocytic function regulates Ab generation in neurons. We identify a novel neuron-specific polarisation of Ab generation controlled by Bin1 and CD2AP. We discover that Bin1 and CD2AP control Ab generation in axonal and dendritic early endosomes, respectively. Both Bin1 loss of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
186
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(210 citation statements)
references
References 94 publications
16
186
2
Order By: Relevance
“…Strikingly SorLA, Bin1, PICALM, and CD2AP, which are linked to increased risk for late onset AD [65,66], all have functions related to endocytosis and endosome trafficking. Ubelmann et al have already shown that depletion of CD2AP inhibits APP and/or CTFs sorting towards ILVs and concomitantly increases Aβ production in post-synaptic endosomes [67]. Exosomal proteins released by neurons within few minutes represent an easily accessible sampling of ILVs.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly SorLA, Bin1, PICALM, and CD2AP, which are linked to increased risk for late onset AD [65,66], all have functions related to endocytosis and endosome trafficking. Ubelmann et al have already shown that depletion of CD2AP inhibits APP and/or CTFs sorting towards ILVs and concomitantly increases Aβ production in post-synaptic endosomes [67]. Exosomal proteins released by neurons within few minutes represent an easily accessible sampling of ILVs.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, however, this class of genes has a secondary consequence of increasing intracellular APP fragments by regulating the levels of APP and/or BACE1 in the early endosome (Dumanis et al, 2015; Fjorback et al, 2012; Miyagawa et al, 2016; Ubelmann et al, 2016) and APP’s amyloidogenic cleavage (Andersen et al, 2005; Dumanis et al, 2015; Fjorback et al, 2012; Miyagawa et al, 2016; Offe et al, 2006; Rogaeva et al, 2007; Thomas et al, 2016; Ubelmann et al, 2016; Xiao et al, 2012) (Fig. 1).…”
Section: Endosomal Traffic Jams Can Occur As An Upstream Eventmentioning
confidence: 99%
“…It is conceivable that the reason why we did not observe any effects of APOE knockdown on Aβ x-40 and Aβ x-42 is because it is expressed mainly by astrocytes and produced only at low amounts by primary neuronal cultures as used for our study. For BIN1, conflicting results have been reported on its role in Aβ regulation: while depletion of BIN1 in neurons resulted in a slight decrease in secreted Aβ 40 with a concomitant increase in intracellular Aβ 40 and Aβ 42 in one study [33], increased levels of secreted Aβ were observed by another group [34] and no effects were detected in neuroblastoma cells in a third study [35]. Similarly, also for PICALM the observed effects on Aβ are diverging: in one study, PICALM was reported to promote Aβ generation in cells and to accelerate Aβ pathology in APP transgenic mice [36] whereas another study observed no effect on cellular Aβ production [37].…”
Section: Resultsmentioning
confidence: 96%